Platform TikTok sebagai Representasi Media Dakwah di Era Digital - Sinta Pratiwi, Clara (Jisab, 2022)
TikTok Platform as a Representation of Da'wah Media in the Digital Age. Tiktok is the most user application during the digital era. With a variety of content, it can reach all circles. One of the positive things that can be used is the potential of tiktok as a da’wah media, especially for young people. One of the tiktok celebrities, Husein Basyaiban, has used his tiktok content for da'wah media to gain 5.4 million followers. This study aims to conduct a semiotic analysis of Husein Basyaiban's account comments and how this tiktok is used as a representation of da'wah media in the digital era. The analysis of the media text used is by using the semiotic analysis of the Charles Sanders Pierce model. The sampling technique in this study was using simple random sampling. Data collection techniques used by researchers are document analysis and library research. This study analyzes the responses of Tiktok netizens regarding the da'wah content uploaded by the @basyaman00 account. The results showed that there were three signs that became the basis of the researcher's analysis on Husein's account. The first is a sign of the large number of comments that appear on Husein's uploaded videos even though the numbers vary. The second is that netizens thank you for the knowledge that has been shared in Husein's video upload. And finally, there is a follow-up question regarding Husein's explanation of a religious problem